2018
DOI: 10.7554/elife.35029
|View full text |Cite
|
Sign up to set email alerts
|

Life in the fast lane

Abstract: Dormice born late in the year start to prepare for winter sooner than mice born earlier in the year.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
(13 reference statements)
0
2
0
Order By: Relevance
“…This is likely to reduce the associated somatic costs of torpor (such as oxidative stress, reduced immunocompetence and neuronal damage[ 21 ]), indicating intraspecific variation of energetics during hibernation. In contrast, other studies [ 9 , 22 25 ] have not found evidence of this.…”
Section: Introductionmentioning
confidence: 66%
“…This is likely to reduce the associated somatic costs of torpor (such as oxidative stress, reduced immunocompetence and neuronal damage[ 21 ]), indicating intraspecific variation of energetics during hibernation. In contrast, other studies [ 9 , 22 25 ] have not found evidence of this.…”
Section: Introductionmentioning
confidence: 66%
“…Life in the fast lane. eLife, 7(June), 40. https://doi.org/10.7554/eLife.35029(Buck, 2018). This article in the American Journal > Watchtime< also describes the clear and expressive design of NOMUS watches.…”
mentioning
confidence: 99%